2022
DOI: 10.1038/s41598-022-21144-0
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation of the mutation rate of Mycobacterium tuberculosis in cases with recurrent tuberculosis using whole genome sequencing

Abstract: The study of tuberculosis latency is problematic due to the difficulty of isolating the bacteria in the dormancy state. Despite this, several in vivo approaches have been taken to mimic the latency process. Our group has studied the evolution of the bacteria in 18 cases of recurrent tuberculosis. We found that HIV positive patients develop recurrent tuberculosis earlier, generally in the first two years (p value = 0.041). The genome of the 36 Mycobacterium tuberculosis paired isolates (first and relapsed isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition to the scenario under active disease, previous studies also demonstrated the accumulation of SNPs and other genomic mutations in the Mtb genome during LTBI. Interestingly, while similar SNP accumulation rates were observed in macaques for LTBI and active disease, the former had a slower rate than the latter in humans ( 7 , 15 18 ). However, whether other characteristics of genomic mutations, including population diversification and signs of selective pressures, are unique to LTBI or similar to active disease remains unknown.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…In addition to the scenario under active disease, previous studies also demonstrated the accumulation of SNPs and other genomic mutations in the Mtb genome during LTBI. Interestingly, while similar SNP accumulation rates were observed in macaques for LTBI and active disease, the former had a slower rate than the latter in humans ( 7 , 15 18 ). However, whether other characteristics of genomic mutations, including population diversification and signs of selective pressures, are unique to LTBI or similar to active disease remains unknown.…”
Section: Introductionsupporting
confidence: 51%
“…4F and G ), while that of all aSNPs was slower in LTBI and active disease. It was reported that the mutation rate of all detected SNPs during LTBI is slower than that during active disease in humans, whereas it was equivalent in macaques ( 7 , 15 18 ). Although our results from synonymous SNPs and all aSNPs comprised reports in macaques and humans, respectively, the sample size is statically small to reach any conclusion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… Mycobacterium tuberculosis is estimated to have an average mutation rate of 0.5 SNPs per genome per year [23], although the mutation rate may be higher in settings with selective pressure of antituberculous therapy, such as in settings of high MDR-TB prevalence [24]. The slow rate of evolution of M.…”
Section: Implementation Challenges Of Tuberculosis Wgs Phylogenymentioning
confidence: 99%
“… Mycobacterium tuberculosis is estimated to have an average mutation rate of 0.5 SNPs per genome per year [ 23 ], although the mutation rate may be higher in settings with selective pressure of antituberculous therapy, such as in settings of high MDR-TB prevalence [ 24 ]. The slow rate of evolution of M. tuberculosis gives rise to relatively few SNPs in clinical isolates, which contributes to the challenge of phylogenetic reconstruction of the evolutionary relationships of clinical isolates [ 25 ], particularly in Singapore’s moderate-incidence setting.…”
Section: Implementation Challenges Of Tuberculosis Wgs Phylogenymentioning
confidence: 99%